2002
DOI: 10.2337/diabetes.51.3.863
|View full text |Cite
|
Sign up to set email alerts
|

Systematic Search for Single Nucleotide Polymorphisms in the Resistin Gene

Abstract: Resistin is a novel polypeptide specifically secreted from adipocytes, and its serum levels are increased in obese diabetic mice. Resistin antagonizes insulin and could account for insulin resistance. To determine whether there are single nucleotide polymorphisms (SNPs) in the resistin gene associated with type 2 diabetes, sequences for 24 Japanese type 2 diabetic patients were initially analyzed using PCR direct sequencing. Three SNPs were found in the introns, but none were present in the coding regions. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
56
1
1

Year Published

2002
2002
2017
2017

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 82 publications
(60 citation statements)
references
References 12 publications
1
56
1
1
Order By: Relevance
“…Several genetic association studies in humans had contradictory results, which can be divided into three categories: (i) an association with obesity but not with diabetes [12,13]; (ii) an association with insulin sensitivity but not with obesity or diabetes [14,15]; and (iii) no association with obesity or with diabetes [16,17,18]. Interestingly, variations in the promoter region of the resistin gene were associated with obesity or insulin resistance [12,15].…”
mentioning
confidence: 99%
“…Several genetic association studies in humans had contradictory results, which can be divided into three categories: (i) an association with obesity but not with diabetes [12,13]; (ii) an association with insulin sensitivity but not with obesity or diabetes [14,15]; and (iii) no association with obesity or with diabetes [16,17,18]. Interestingly, variations in the promoter region of the resistin gene were associated with obesity or insulin resistance [12,15].…”
mentioning
confidence: 99%
“…Resistin expression was low and not significantly different among human fat cells from unaffected, insulin-resistant, and type 2 diabetic patients (21), and mRNA levels in human adipocytes were not correlated with BMI (22). No significant associations have been found between resistin gene variants and type 2 diabetes (23,24). Although we have shown that variation in the resistin gene is unlikely to be responsible for the association and linkage with PCOS that we find in this region, these findings do not eliminate the possible importance of resistin in the etiology of PCOS, especially in view of the insulin sensitivity defects.…”
Section: Discussionmentioning
confidence: 94%
“…PCR direct sequencing was performed as described previously with the following modifications (13,14). Genomic DNA was extracted from leukocytes using a DNA Isolation Kit for Mammalian Blood (Boehringer Mannheim, Indianapolis, IN).…”
Section: Methodsmentioning
confidence: 99%